Novo conjunto de indicadores de desempenho operacional para redes elétricas inteligentes por meio da Lógica fuzzy - Rodrigues, Mauro Fonseca (2020)
Operational performance analysis is a multidisciplinary tool that allows the engineering systems manager to control the quality of services provided, as needed. For this operational tool to be effective, it is necessary to know the details of the processes involved and mathematically model metrics that bring representative responses from the goals established for the qualification of the system. In this work, the quality metrics established for the Telecommunications systems and the continuity of the Electricity Distribution services, inspected by Anatel and Aneel, respectively, were analyzed. The two methods have differences in schedules, evaluated periods and mathematical relationships. The two methods have differences in schedules, evaluated periods and mathematical relationships. In addition, they have few indexes listing their indicators. Thus, Fuzzy Logic was selected as a mathematical tool to relate the indicators currently practiced in order to create more comprehensive indices that can compose a new methodology for the analysis of operational performance for Smart Grids (REI). This methodology starts from the union of the current sets with their respective metrics, being organized in four main axes: specific indices, instant monitoring indices, new indicators and customer satisfaction. From these groups, indicators and indexes were developed to assess the quality of REI. Then, for the first grouping: indexes of establishment and continuity of data connection (REI01) and guarantee of the contracted transmission rate (REI02) and infrastructure quality indicator (REI07); for the second: indices of instantaneous capacity of individual interruptions (REI03), of instantaneous ability to calculate the frequency of individual interruptions (REI04), of instantaneous capacity of collective interruptions (REI05), of instantaneous ability to calculate the frequency of interruptions individual (REI06); for the third: indicators of the instantaneous data transfer rate (SMP10i / SCM4i) and the average monthly individual data transfer rate (SMP11i / SCM5i); and, for the fourth: the union of several current indicators and indices that make up customer satisfaction, such as drop rate (SMP7), maximum duration of continuous interruption (DMIC), user complaints rate (REL), number repair requests (RAI), consumer satisfaction Aneel (IASC), satisfaction survey and perceived quality Anatel (SCM and SMP). Equal data with different goals per company (DIC, for example) were normalized through the Indicator Unit Value (VUI) created. Through the Fuzzy Logic it was possible to implement the evaluation of the inputs from the goals stipulated by the current regulations, in levels established as stages or equivalent numerical quality levels, being: very bad (0 - 0.3), bad (0.2 - 0 , 6), good (0.5 - 0.9) and excellent (0.8 - 1). The fuzzifiers and defuzzifiers were tested with a REI, found in the bibliography, and with real data from a Brazilian region with an implanted REI, showing adherence in the evaluations and results obtained.